The Association Between Obesity and Low Back Pain and Disability Is Affected by Mood Disorders: A Population-Based, Cross-Sectional Study of Men. Issue 15 (April 2016) - Chou, Louisa; Brady, Sharmayne R.E.; Urquhart, Donna M.; Teichtahl, Andrew J.; Cicuttini, Flavia M.; Pasco, Julie A.; Brennan-Olsen, Sharon L.; Wluka, Anita E.
Abstract : Abstract: Low back pain (LBP) and obesity are major public health problems; however, the relationship between body composition and low back pain in men is unknown. This study aims to examine the association between body composition and LBP and disability in a population-based sample of men, as well as the factors that may affect this relationship. Nine hundred seventy-eight male participants from the Geelong Osteoporosis Study were invited to participate in a follow-up study in 2006. Participants completed questionnaires on sociodemographics and health status. Low back pain was determined using the validated Chronic Back Pain Grade Questionnaire and the presence of an emotional disorder was assessed using the Hospital Anxiety Depression Scale. Body composition was measured using dual energy x-ray absorptiometry. Of the 820 respondents (84% response rate), 124 (15%) had high-intensity low back pain and/or disability (back pain). Low back pain was associated with higher body mass index (28.7 ± 0.4 vs 27.3 ± 0.2 kg/m 2, P = 0.02) and waist–hip ratio (0.97 ± 0.006 vs 0.96 ± 0.006, P = 0.04), with increased tendency toward having a higher fat mass index (8.0 vs 7.6 kg/m 2, P = 0.08), but not fat-free mass index ( P = 0.68). The associations between back pain and measures of obesity were stronger in those with an emotional disorder, particularly for waist–hip ratio ( P = 0.05 for interaction) and fat mass index ( P = 0.06 for interaction). In a population-based sample of men, high-intensity LBP and/or disability were associated with increased levels of obesity, particularly in those with an emotional disorder. This provides evidence to support a biopsychosocial interaction between emotional disorders and obesity with low back pain.